2019
DOI: 10.1148/radiol.2018180883
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Electronic Release of Imaging Results through an Online Patient Portal

Abstract: To determine an optimal embargo period preceding release of radiologic test results to an online patient portal. Materials and Methods: This prospective discrete choice conjoint survey with modified orthogonal design was administered to patients by trained interviewers at four outpatient sites and two institutions from December 2016 to February 2018. Three preferences for receiving imaging results associated with a possible or known cancer diagnosis were evaluated: delay in receipt of results (1, 3, or 14 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Should this information be released to the patient before the physician has had a chance to review test results and pathology reports with the patient? In a survey of 464 patients, Woolen and colleagues found that patients “prefer to receive imaging results associated with a cancer diagnosis as soon as possible, from their physician, and over the telephone” [ 18 ]. We now hold pathology reports with a cancer diagnosis for 3 days, allowing time for the clinician to contact the patient.…”
Section: Information Blockingmentioning
confidence: 99%
“…Should this information be released to the patient before the physician has had a chance to review test results and pathology reports with the patient? In a survey of 464 patients, Woolen and colleagues found that patients “prefer to receive imaging results associated with a cancer diagnosis as soon as possible, from their physician, and over the telephone” [ 18 ]. We now hold pathology reports with a cancer diagnosis for 3 days, allowing time for the clinician to contact the patient.…”
Section: Information Blockingmentioning
confidence: 99%
“…In one study, patients' preferred direct physician communication particularly for the return of abnormal biopsy results (85) though other studies reported participant indifference to communication method (81,101) and one study reported preference for return of biopsy results via the telephone rather than in-person (102). As waiting time for in-person care increased, patients became more willing to accept electronic communication regarding health information (54,55,70,85). Patients also expressed preferences for different modalities and functionalities of HIT based on the information being communicated (e.g., preference for text message vs. email) (87,(98)(99)(100).…”
Section: Communication Modality Preferences Depend On the Type Of Exchangementioning
confidence: 99%
“…Woolen and colleagues (1) commented that patients preferred communication with their physicians rather than with the radiologist and others have published similar conclusions (8). However, some patients might like the option to contact the radiologist in certain circumstances or when they are having difficulty reaching their physician.…”
mentioning
confidence: 95%
“…I n this issue of Radiology, Woolen et al (1) describe several important findings related to patients' communication with their doctors and how quickly they receive imaging results. This study is important because of the controversies surrounding the release of imaging reports with and without referring physician control.…”
mentioning
confidence: 99%